Penggunaan Follicle Stimulating Hormone dan Pregnant Mare Serum Gonadotrophin untuk Superovulasi pada Sapi Persilangan Brahman - Adriani Adriani; B Rosadi; Depison Depison (Faculty of Animal Science, Bogor Agricultural University, 2009)
Twenty cattle were used in this experiment to determine the effect of administration follicle stimulating hormone (FSH) and pregnant mare serum gonadotrophin (PMSG) hormones on superovulation of Brahman cross cattle. The experiment was designed into completely randomized design with 5 treatments as follows. Treatments 1 (T1): 4 mg of FSH was injected twice a day intra-ovary, T2: 8 mg of FSH was injected twice a day intra-ovary, T3: 300 IU of PMSG was injected single dose intra-ovary, T4: 600 IU of PMSG was injected single dose intra-ovary, T5: 40 mg of FSH was injected intramuscular. All experimental cattle were oestrus synchronized using 15 mg of PGF2α twice at 11-days intervals. Number of corpus luteum (CL) was detected by rectal palpation at day-7 after artificial insemination. Results showed that 19 cattle (95%) indicated oestrus sign. Eleven cattle (57.9%) showed oestrus sign 2 days after PGF2α injection and the rest 8 cattle (42.1%) oestrus sign was detected at 3 days after PGF2α injection. FSH and PMSG treatments increased significantly (P < 0.05) number of CL. The highest CL number was found in T5, meanwhile number of CL in T2 and T4 were higher compared to T1 and T3. The average treatment effect could produce 6.8±5.42 CL with range 2–26 CL. On the other hand single dose treatment of 600 IU PMSG (T4) showed high significant number of non ovulatory (persistent) follicle compared to other treatments (T1, T2, T3 and T5) on average number of persistent follicle 2.0±1.97 from 19 cattles. It is concluded that the best superovulation treatment was produced by injection 40 mg of FSH intra-musculary. Key words: Brahman cross, corpus luteum, PMSG, FSH